Visceral Adiposity Index is a predictor of incident colorectal cancer: a population-based longitudinal study - Michiaki Fukui; Masahide Hamaguchi; Yoshitaka Hashimoto; Akihiro Obora; Takao Kojima; Takuro Okamura (BMJ Open Gastroenterology)
Objective The Visceral Adiposity Index (VAI) is a marker of visceral fat accumulation and dysfunction. We aimed to investigate the association between VAI and incident colorectal cancer (CRC).Design In this historical cohort study of 27 921 (16 434 men and 11 487 women) participants, we divided the participants into tertiles according to VAI. We calculated VAI: men, VAI = (waist circumference (WC)/(39.68+1.88 × body mass index (BMI))) × (triglycerides (TG)/1.03) × (1.31/high-density lipoprotein cholesterol (HDL)); women, VAI = (WC/(36.58+1.89 × BMI)) × (TG/0.81) × (1.52/HDL). We performed Cox proportional hazard models, adjusting for sex, age, smoking, alcohol consumption, exercise, haemoglobin A1c and systolic blood pressure.Results During the median 4.4-year follow-up, 116 participants developed CRC. Compared with the lowest tertile, the HRs of incident CRC in the middle and the highest tertiles were 1.30 (95% CI 0.76 to 2.28, p=0.338) and 2.41 (1.50 to 4.02, p<0.001) in univariate analysis. Moreover, the HRs of incident CRC in the middle and the highest tertiles were 1.27 (0.73 to 2.23, p=0.396) and 1.98 (1.15 to 3.39, p=0.013) after adjusting for covariates.Conclusions VAI can be a predictor of incident CRC. For early detection, we should encourage people with high VAI to undergo screening for CRC.